Severe metabolic alkalosis due to diuretic treatment in a patient with distal renal tubular acidosis: a rare association - Lucaccioni, Laura; Coccolini, Elena; Dozza, Alessandra; Cantatore, Sante Lucio; Berardi, Alberto; Predieri, Barbara; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Distal renal tubular acidosis is a rare genetic disease, characterised by deficit in renal tubular transport. Clinical features are metabolic acidosis with hypercloraemia and hypokalemia, and inability in urine acidification. Hypercalciuria may also be present, often treated with the use of a diuretic therapy with thiazides. Case Presentation: We present a severe disease onset in a neonate with consanguineous parents, both autosomal-recessive for an ATP6VOA4 gene mutation, and a nevertheless severe episode of metabolic alkalosis, occurred in the same patient after few months, during the diuretic therapy. Conclusion: Biochemical results lead us to hypothesize a susceptibility to the treatment that need further investigations.